Systemic evaluation of integrated farming in semi-arid Bundelkhand: Economic, employment and sustainability outcomes - Aniket, K; Chaubey, A K; Ajeet, S; Harshad, M; Narendra, S; Yash, G; Manish, K S; Singh, Shyam; Dinesh, S; Panwar, G S; et al. (Plant Science Today, 2026)
This study presents a comprehensive three-year (2021–2024) evaluation of a 1.00 ha Integrated Farming System (IFS) model established at Banda University of Agriculture and Technology, Banda, with support from National Bank for Agriculture and Rural Development (NABARD). The model integrated fourteen farm-based enterprises, including cropping, vegetables, fruits, fodder, dairy, poultry, duckery, farm pond-based fishery, mushroom, honeybee, organic recycling, low-cost nursery, post-harvest processing and solar energy, to address the economic and ecological challenges of semi-arid rainfed farming systems. Component-wise analysis revealed substantial variation in profitability and economic viability among the enterprises. Fishery emerged as the most profitable enterprise, with a net return of ₹222174 and a benefit-cost ratio (BCR) of 1.70, followed by organic recycling, the cropping system and dairy units. In contrast, enterprises such as duckery, mushroom cultivation and beekeeping performed poorly due to climatic unsuitability and market-related constraints. The cumulative gross return over the three-year period was ₹2089753, with a net return of ₹525347, despite capital investments being amortized over a ten-year period. Employment generation potential was substantial, contributing to enhanced livelihood opportunities in the region. When income from family labour and savings from solar electricity (₹131754) were included, the overall benefit-cost ratio improved from 0.34 to 0.69. Optimization analysis identified eight shortlisted components that exhibited superior economic performance and employment generation potential. The integrated system showed a BCR of 1.18 when livelihood contributions were included. Overall, the study underscores that strategic enterprise integration, internal input generation and diversification significantly enhance the sustainability and resilience of IFS models. It concludes that context-tailored IFS approaches can significantly improve livelihood security, farm productivity and ecological sustainability in resource-constrained dryland regions like Bundelkhand.